FREQUENCY AND TYPES OF BODILY MEDICO-LEGAL INJURIES IN A RURAL AREA - Seema, Nighat; Ahmad, Iftikhar; Mughal, Salim; Khan, Delawar; Khan, Omair (Journal of Ayub Medical College Abbottabad, 2010)
Background: The primary objective of the study was to know the types and frequency of the bodily medico legal injuries in a rural setup. Methods: Data was retrospectively collected by selecting 55 cases consecutively. Data of injury types was analysed. Results: The number of injured males in this study was 48 (87.3%) while the females were 7 (12.7%). The most common type of injuries were shajja (45.9% among males and 71.4% among females). Conclusions: Our study shows relatively true picture of frequency and types of injuries. It was observed that male population is more prone to violence than females owing to the conservative life style of women in our society. Keywords: bodily medico-legal injuries, Shajja